Total Syntheses of Sarcandrolide J and Shizukaol D: Lindenane Sesquiterpenoid [4+2] Dimers. (2nd December 2016) - Yuan, Changchun; Du, Biao; Deng, Heping; Man, Yi; Liu, Bo
Abstract: The syntheses of members of a family of lindenane sesquiterpenoid [4+2] dimers led to the total syntheses of sarcandrolide J and shizukaol D. Inspired by a modified biosynthetic pathway, a cascade featuring furan formation/alkene isomerization/Diels–Alder cycloaddition was devised to construct the congested polycyclic architecture of the target molecules with the correct stereochemistry. This study presents a pioneering synthetic entry to this family of natural products and paves the way for fully exploring their biological functions.